例
\(A=
\left(\begin{array}{cc}
2 & 1\cr
2 & 3\cr
\end{array}\right)\),
\(P=\left(\begin{array}{cc}
1 & 1\cr
-1 & 2\cr
\end{array}\right)\) について,
\(P^{-1}AP=
\left(\begin{array}{cc}
1 & 0\cr
0 & 4\cr
\end{array}\right)\)
左辺の n 乗は面白くて
\((P^{-1}AP)^2=
P^{-1}APP^{-1}AP=P^{-1}A^2P\)
繰り返して,
\((P^{-1}AP)^n=P^{-1}A^nP\)
右辺の n 乗は対角行列のべきだから
\(
\left(\begin{array}{cc}
1 & 0\cr
0 & 4\cr
\end{array}\right)^n=
\left(\begin{array}{cc}
1 & 0\cr
0 & 4^n\cr
\end{array}\right)
\)
したがって,
\(P^{-1}A^nP=
\left(\begin{array}{cc}
1 & 0\cr
0 & 4^n\cr
\end{array}\right)\)
ゆえに
\(A=P
\left(\begin{array}{cc}
1 & 0\cr
0 & 4^n\cr
\end{array}\right)P^{-1}\)
\(=\dfrac{1}{3}
\left(\begin{array}{cc}
1 & 1\cr
-1 & 2\cr
\end{array}\right)\left(\begin{array}{cc}
1 & 0\cr
0 & 4^n\cr
\end{array}\right)\left(\begin{array}{cc}
2 & 1\cr
-1 & 1\cr
\end{array}\right)\)
\(=\dfrac{1}{3}
\left(\begin{array}{cc}
2+4^n & -1+4^n\cr
-2+2\cdot 4^n & 1+2\cdot 4^n\cr
\end{array}\right)
\)